2020
DOI: 10.1186/s12874-020-0905-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and pathways to impact in public health research: a preliminary analysis of research funded by the National Institute for Health Research (NIHR)

Abstract: Background: The mechanisms and pathways to impacts from public health research in the UK have not been widely studied. Through the lens of one funder (NIHR), our aims are to map the diversity of public health research, in terms of funding mechanisms, disciplinary contributions, and public health impacts, identify examples of impacts, and pathways to impact that existing reporting mechanisms may not otherwise have captured, and provide illustrations of how public health researchers perceive the generation of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 35 publications
4
16
0
Order By: Relevance
“…Whilst [ 17 ] found that researchers questioned the type of evidence needed from public health research to inform policy, our findings suggest that researchers were aware of the type of evidence needed and were using non-standard research designs to ensure that the research generated relevant evidence. Evidence derived from realist reviews, natural experiments, non-randomised trials, novel statistical methods and complex systems approaches provide alternative ways to explore complex interventions [ 26 , 29 ] and some of these approaches were used by the researchers.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Whilst [ 17 ] found that researchers questioned the type of evidence needed from public health research to inform policy, our findings suggest that researchers were aware of the type of evidence needed and were using non-standard research designs to ensure that the research generated relevant evidence. Evidence derived from realist reviews, natural experiments, non-randomised trials, novel statistical methods and complex systems approaches provide alternative ways to explore complex interventions [ 26 , 29 ] and some of these approaches were used by the researchers.…”
Section: Discussionmentioning
confidence: 83%
“…The interviewer and note-taker undertook the interviews together in a private room at the NIHR Evaluation, Trials and Studies Coordinating Centre in Southampton. The interview framework was adapted from [ 17 ], which aligned to the Payback Framework, and sought to understand the nature of the influence or impact the research had realised. However, it also sought to understand how change came about or what stopped it, thereby investigating the way in which knowledge from research was mobilised.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensuring implementation research is participatory, by creating opportunities involving engagement with key stakeholders, is key to achieving that change. Several other disciplines have described such processes, including 'knowledge mobilisation', 63 the use of 'embedded researchers', 64 'co-production' methods between researchers and practitioners, 65 as well as studies examining how societal impact stems from research. 63 66 67 Generally these are intended to create opportunities for stakeholders to understand, adopt and sustain outcomes 68 These activities can be parts of intervention design itself (ie, in codesign or coproduction activities), and at other times they are activities occurring in parallel to the research and considered to be activities which complement the research process in facilitating its adoption and scale-up.…”
Section: Engagement and Knowledge Exchange Activitiesmentioning
confidence: 99%
“…Ensuring implementation research is participatory, by creating opportunities involving engagement with key stakeholders, is key to achieving that change. Several other disciplines have described such processes, including 'knowledge mobilisation', 63 the use of 'embedded researchers', 64 'co-production' methods between researchers and practitioners, 65 as well as studies examining how societal impact stems from research. 63 66 67 Generally these are intended to create opportunities for stakeholders to understand, adopt and sustain outcomes BMJ Global Health from research, or create opportunities for 'productive interactions'.…”
Section: Engagement and Knowledge Exchange Activitiesmentioning
confidence: 99%